Prognostic utility of the C-reactive protein–albumin–lymphocyte (CALLY) index in metastatic renal cell carcinoma - Güner Akgüner; Mustafa Altınbaş (BMC Cancer)
Abstract Background and objective The CALLY index has been recognized as a prognostic biomarker across various malignancies; however, its prognostic utility in metastatic renal cell carcinoma (mRCC) has not been extensively characterized. This study aimed to elucidate the prognostic significance of the C-reactive protein–albumin–lymphocyte (CALLY) index in patients diagnosed with mRCC. Methods In this retrospective multicenter study, patients with metastatic renal cell carcinoma were included. Demographic and disease-related data were collected. The CALLY index was calculated as follows: serum albumin level (g/dL) × absolute lymphocyte count (cells/µL)/C-reactive protein (CRP) (mg/dL) × 104. The optimal cut-off value for the CALLY index was determined using maximal log-rank analysis. Overall survival and progression-free survival analyses were performed according to the cut-off value, and Cox regression analyses were conducted to identify factors affecting prognosis. Results A total of 95 patients were included in the present study. The prognostic cut-off value for the CALLY index was determined as 0.12. The median overall survival (OS) was 11.1 months (95% CI 6.7–15.4) in the CALLY index < 0.12 group, compared to 45.7 months (95% CI 31.6–59.8) in the CALLY index ≥ 0.12 group (p < 0.001). Similarly, the median progression-free survival (PFS) was 7.1 months (95% CI 4.5–13.2) in the CALLY index < 0.12 group and 33.1 months (95% CI 17.2–48.1) in the CALLY index ≥ 0.12 group (p < 0.001). In Cox regression analysis, a CALLY index < 0.12 was identified as an independent prognostic factor for shorter OS (HR: 0.41, 95% CI 0.22–0.76, p = 0.004) and PFS (HR: 0.40, 95% CI 0.23–0.69, p = 0.001). Conclusion The CALLY index was identified as an independent prognostic biomarker in metastatic renal cell carcinoma. Prospective large-scale studies are needed to confirm its clinical utility.